2019
DOI: 10.3390/nu11081953
|View full text |Cite
|
Sign up to set email alerts
|

How Lifestyle Factors Affect Cognitive and Executive Function and the Ability to Learn in Children

Abstract: In today’s research environment, children’s diet, physical activity, and other lifestyle factors are commonly studied in the context of health, independent of their effect on cognition and learning. Moreover, there is little overlap between the two literatures, although it is reasonable to expect that the lifestyle factors explored in the health-focused research are intertwined with cognition and learning processes. This thematic review provides an overview of knowledge connecting the selected lifestyle factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 225 publications
(262 reference statements)
1
72
0
4
Order By: Relevance
“…A lack of dietary variety in childhood leads to enduring impacts on both physical and cognitive health (Evans et al, 2018 ). Consequently, establishing healthy dietary habits in childhood is crucial in preventing long-term repercussions (Jirout et al, 2019 ). Food rejection, namely food neophobia and pickiness, has been determined as a central psychological driver in reduced dietary variety in young children (Carruth et al, 2004 ; Levene and Williams, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A lack of dietary variety in childhood leads to enduring impacts on both physical and cognitive health (Evans et al, 2018 ). Consequently, establishing healthy dietary habits in childhood is crucial in preventing long-term repercussions (Jirout et al, 2019 ). Food rejection, namely food neophobia and pickiness, has been determined as a central psychological driver in reduced dietary variety in young children (Carruth et al, 2004 ; Levene and Williams, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The eighth-grade year participants' data, were analyzed, yielding a 9720 data point sample size. Researchers used linear regression analyses to assess the relationship among nutrition, physical activity, and academic achievement, while controlling for socioeconomic status, age, and sex [25,26]. In Norway, researchers demonstrated that regular meal pattern, healthy food consumption and physical activity were all associated with increased odds of high academic achievement in Norwegian adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, consumption of unhealthy foods and beverages, was associated with decreased odds of high academic achievement [27]. Researchers in the US concluded that non-active, unhealthy nutrition, participants scored consistently lower for reading, math, and science standardized tests when compared to those classified as active, healthy nutrition regardless of sex [25,26]. Furthermore, research in Australia focusing on secondary analysis to examine associations between a range of dietary behaviors and children s academic achievement, revealed that dietary behaviors are associated with higher academic achievement [28].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in physical activity may also have an impact on student concentration. The systematic review article written by Jirout et al (2019) academic functions. The article also mentions that several studies have found that aerobic fitness is closely related to improving cognitive and learning abilities in children (Jirout et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review article written by Jirout et al (2019) academic functions. The article also mentions that several studies have found that aerobic fitness is closely related to improving cognitive and learning abilities in children (Jirout et al, 2019). (A parenting educator in Australia also stated that learning breaks filled with exercise or exercise can increase concentration in children (Grose,2009).…”
Section: Discussionmentioning
confidence: 99%